A study of determinations of social media marketing towards acceptance of Takaful products / Nurul Safinah Mat Nawi - Mat Nawi, Nurul Safinah (2017)
Nowadays, Takaful products has growth rapidly and it has been widely spread in both Muslim and non-Muslim countries. In order to encourage more acceptance by people, Takaful industry need to use social media as a medium to build awareness about Takaful product. Social media gained precedence in today’s business environment, and consumers themselves are more receptive to this marketing media. This research a study of determinants of social media marketing towards acceptance of Takaful products had been conducted to analyze the relationship among determinants of social media marketing. There are three independent variables of this research which is trust on social media, interactive on social media and advertisement characteristics in social media towards acceptance of Takaful products. This research has been answered by 135 respondents through questionnaire. By using application Statistical Package for the Social Science (SPSS) version 20 has been used to analyze the data. Based on the study, the results shows there are significant relationship between trust on social media marketing and advertising characteristics towards acceptance Takaful products